Reusability Study of Sulfated Zirconia Functionalized SBA-15 Catalyst for Biolubricant Oil Production from Oleic Acid - F R Rangganita; Lilis Hermida; A Angraeni; D Khoirunnisa (Journal of Engineering and Scientific Research, 2019)
Sulfated zirconia functionalized SBA-15 catalsyt (SZr-SBA-15) was prepared by reacting SBA-15 with Zirkoniumoxychloride and urea at 90oC to form ZrO2-SBA-15. Then, ZrO2-SBA-15 was reacted with H2SO4 at room temperature to produce SZr-SBA-15 catalsyt.. The catalyst was characterized in terms of adsorptiondesorption nitrogen analysis, SEM-EDX and FTIR. Based on SEM-EDX and adsorption-desorption nitrogen analysis results, it was found that Zr had been incorporated in SBA-15. By using the SZr-SBA-15 catalyst, esterification reaction of oleic acid with TMP to produce biolubricant oil of Trimethylolpropanetrioleat achieved 85% oleic acid conversion and selectivity of 63,7%. Reusability study of SZr-SBA-15 catalyst was carried out for 3 rounds of reaction. It was found that the catalyst could be used up to 3 rounds without significant decrease in activity